2021
DOI: 10.1111/are.15586
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of ration levels and temperature on immune responses of the triangle sail mussel Hyriopsis cumingii

Abstract: Nowadays, the cultivation mode of Hyriopsis cumingii urgently needs transformation and upgrading, and realizing sustainable aquaculture lacks the selection of suitable algae and the exploration of culture conditions. This experiment is to evaluate combined effects of ration levels (low ration, medium ration and high ration) and temperature (13.0 ± 0.2°C, 23.0 ± 0.2°C, and 33.0 ± 0.2°C) on immune responses of H. cumingii. Activities of immune enzymes (alkaline phosphatase, superoxide dismutase, catalase and lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…During the acclimatization period, mussels were fed with N. pelliculosa at biomass 4 × 10 4 cells mL − 1 ca. 12.5 mg L − 1 , which was according to results of the preliminary experiment (Sun et al, 2021).…”
Section: Experimental Algae and Musselssupporting
confidence: 58%
See 1 more Smart Citation
“…During the acclimatization period, mussels were fed with N. pelliculosa at biomass 4 × 10 4 cells mL − 1 ca. 12.5 mg L − 1 , which was according to results of the preliminary experiment (Sun et al, 2021).…”
Section: Experimental Algae and Musselssupporting
confidence: 58%
“…Therefore, the present study detected above biochemical parameters in H. cumingii exposed to different ration levels and temperatures, providing insight into metabolic performance, growth and physiological status. Our previous research found that uncomfortable food and temperature levels increased activities of immune enzymes and expression of immune genes in a short time, but when it exceeded the immune regulatory range, it caused immune damage of H. cumingii (Sun et al, 2021). We hypothesized that different ration levels and temperatures also affects the digestive and metabolic physiology of H. cumingii.…”
Section: Introductionmentioning
confidence: 93%
“…Lysozyme is a typical humoral defense component, a large number of experiments have studied its role and mechanism in the immune response of marine bivalves (Muroga and Takahashi, 2007;Hu et al, 2015;Sun et al, 2022). The action mechanism of lysozyme mainly lies in its ability to destroy peptidoglycan components in dissolved bacterial cell wall, thus causing bacterial cell wall damage and disintegration (Liu et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…Indeed, global warming poses a serious threat to global aquaculture production [ 4 ]. Rising water temperature has a series of deleterious effects on the immunity [ 2 , 5 ], metabolism [ 6 , 7 ], reproduction and development [ 8 , 9 ], and behavioral patterns [ 10 , 11 ] of aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater ecosystems are particularly fragile under the scenario of global change [ 17 ]. Previous studies have found that high-temperature stress has many adverse effects on freshwater mollusks [ 5 , 18 , 19 , 20 , 21 ] and is a key factor that causes mass mortality [ 21 ]. To date, few studies have focused on the adverse impacts of thermal stress on C. cathayensis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%